State complexity of basic operations on suffix-free regular languages - Han, Yo-Sub; Salomaa, Kai (MATHEMATICAL FOUNDATIONS OF COMPUTER SCIENCE 2007, PROCEEDINGS, 2007)
We investigate the state complexity of basic operations for suffix-free regular languages. The state complexity of an operation for regular languages is the number of states that are necessary and sufficient in the worst-case for the minimal deterministic finite-state automaton that accepts the language obtained from the operation. We establish the precise state complexity of catenation, Kleene star, reversal and the Boolean operations for suffix-free regular languages.